2013
DOI: 10.1007/s10714-013-1561-6
|View full text |Cite
|
Sign up to set email alerts
|

Rotating effects on the Dirac oscillator in the cosmic string spacetime

Abstract: In this contribution, we study the Dirac oscillator under the influence of noninertial effects of a rotating frame in the cosmic string spacetime. We show that both noninertial effects and the topology of the cosmic string spacetime restrict the physical region of the spacetime where the quantum particle can be placed, and discuss two different cases of bound states solutions of the Dirac equation by analysing the behaviour of the Dirac oscillator frequency.Comment: 15 pages. In General Relativity and Gravitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 64 publications
0
95
1
Order By: Relevance
“…The Dirac oscillator was investigated for a spin-1/2 particle in the presence of topological defects in Refs. [10][11][12][13][14][15][16][17][18]. However, these studies were carried out for the quantum dynamics of spin-1/2 particles, leaving a gap in the treatment of harmonic interaction for relativistic scalar particles.…”
Section: Introductionmentioning
confidence: 99%
“…The Dirac oscillator was investigated for a spin-1/2 particle in the presence of topological defects in Refs. [10][11][12][13][14][15][16][17][18]. However, these studies were carried out for the quantum dynamics of spin-1/2 particles, leaving a gap in the treatment of harmonic interaction for relativistic scalar particles.…”
Section: Introductionmentioning
confidence: 99%
“…Then, let us consider the particular case which α 2 s ≫ 1, while the ρ 0 and the parameter of the confluent hypergeometric function b are fixed and that the parameter of the confluent hypergeometric function a to be large. In the way, a confluent hypergeometric function can be written in the form [54,58,59]:…”
Section: Effects Of a Hard-wall Potentialmentioning
confidence: 99%
“…Various studies on the electromagnetic dynamics of the magnetic and electric dipole moments shown that both their global and local physical properties can be sensitive to non-trivial geometries [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However, it is still difficult to observe them experimentally.…”
Section: Hua-wei Fanmentioning
confidence: 99%